2013
DOI: 10.1177/1367493513496668
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of caring for a child with a chronic disease

Abstract: Chronically ill children require several hours of additional care per day compared to healthy children. As parents provide most of this care, they have to incorporate it into their daily schedule, which implies a reduction in time for other activities. The study aimed to assess the effect of having a chronically ill child on parental employment and parental leisure activity time, and to explore the role of demographic, social, and disease-related variables in relation to employment and leisure activities. Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 28 publications
(39 reference statements)
4
52
0
1
Order By: Relevance
“…32,33 Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health. 34 The income derived from work and total income were found to be persistently lower for the mothers of children with cancer compared with reference mothers after approximately 3 years, but such differences were not observed in fathers. In couples, the division of caregiving responsibilities is often skewed, with women assuming a caregiving role more often than men due to gendered norms and habits.…”
Section: Income and Social Benefits Trajectories/hiyoshi Et Almentioning
confidence: 88%
See 1 more Smart Citation
“…32,33 Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health. 34 The income derived from work and total income were found to be persistently lower for the mothers of children with cancer compared with reference mothers after approximately 3 years, but such differences were not observed in fathers. In couples, the division of caregiving responsibilities is often skewed, with women assuming a caregiving role more often than men due to gendered norms and habits.…”
Section: Income and Social Benefits Trajectories/hiyoshi Et Almentioning
confidence: 88%
“…Psychological distress and feelings of uncertainty, helplessness, and loneliness may compromise health and increase disease risk . Limited participation in work during periods spent caring for children also may lead to the loss of personal satisfaction, social networks, and possibly respite from home and care responsibilities, which also may damage health …”
Section: Discussionmentioning
confidence: 99%
“…Four of these examined rates of employment in parents of a child with numerous chronic conditions. For example, Hatzmann et al () found that parents of chronically ill children (0 to 18 years) were less likely to work more than 20‐hr weeks than were parents of healthy children (odds ratio = .71). Amongst parents of chronically ill children, a negative association was found between the dependency of the child on daily care and low parental educational level with family and maternal employment.…”
Section: Resultsmentioning
confidence: 99%
“…In relation to health and well‐being, 35% of families reported serious physical and psychological problems with 36% reporting sleep disruptions at night because of the child's asthma. Similarly, having a child with a chronic illness was reported to be negatively associated with participating in leisure activities for parents (Hatzmann et al, ). On average, these parents were found to spend around 9% fewer hours in leisure activities than parents of healthy children.…”
Section: Resultsmentioning
confidence: 99%
“…We know that in the Netherlands, the division of caregiving roles is still very “traditional.” According to data of Statistics Netherlands, more than 80% of the employed mothers in a relationship work part‐time, against 14% of the fathers . Furthermore, results of a Dutch study in parents of children with a chronic illness showed that caring for an ill child leads to an even wider gap between maternal and paternal labor force participation . Additionally, a recent study in parents of long‐term childhood cancer survivors showed greater dependency in the parental relationship as compared to population‐based controls, with mothers being the primary caregivers and fathers the breadwinners …”
Section: Discussionmentioning
confidence: 99%